PENGGUNAAN ANTIBIOTIK PADA TERAPI DIARE AKUT ANAK DI INSTALASI RAWAT JALAN PUSKESMAS BENDAN TAHUN 2012 - Isti Agitsah; Siska Rusmalina; Jamaludin Al J. Ef (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Diarrhea  disease  cause    death  third  of    children  in  the  world. The  main  causes  diarrhea  death  is improper  therapy  management. To  minimize  the  number  of  deaths  due  to  diarrhea,  especially  in the town of  Pekalongan, so  necessary to do research to know  percentage of antibiotic use and percentage  types  of  antibiotics  used  in  therapy  of  acute  diarrhea  children  at  installation  of outpatient  health  centers  bendan  Pekalongan  city    in  2014.  The  method  used  in  this  study  was descriptive  with  reference  to  secondary  data  retrieved  from  the  medical  records.  Results  of  this study  was  the  percentage  of  antibiotics  used  in  the  treatment  of  acute  diarrhea  in  children outpatient health centers poly Bendan Pekalongan is 83.59%. consisting of 92.63% cotrimoxazole, chloramphenicol was 2.76%, 1.84% metronidazole is, tetracycline was 0.69%, 0.69% gentamicin is,  0.46%  of  amoxicillin,    and  0.23%  respectively  for  cefadroxil,    neomycin,  erythromycin  also ketokonazole. Thus the treatment of acute diarrhea children in  Outpatient Health Center Bendan Installation  Pekalongan  are  appropriate  and  meet  the  requirements  of  Basic  Medicine  in  health centers and BKPM (Public Lung Health Center). Keywords: Antibiotic, Acute Diarrhea, Children, health center